2017
DOI: 10.5888/pcd14.160506
|View full text |Cite
|
Sign up to set email alerts
|

Teach Our Children: Stroke Education for Indigenous Children, First Nations, Ontario, Canada, 2009–2012

Abstract: BackgroundBecause of the heightened risk for stroke among indigenous people, we conducted this multiyear community case study from 2009 through 2012 to address stroke education needs among children aged 11 to 13 years residing in northern urban, rural, and remote First Nations in Ontario, Canada. The goal was to determine what young people understand about stroke and to develop an age-appropriate and culturally appropriate educational product.Community ContextThis project responded to First Nations requests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The use of tuakana and kaiarahi is consistent with the literature on community health workers (CHW) [51,52]. CHW are frequently employed with Indigenous communities in order to connect culturally with participants and systematic reviews demonstrate positive health gains from interventions delivered by CHW [31,32]. The current findings are also supportive of the benefits of using participatory research approaches to develop and adapt lifestyle interventions for risk factors associated with diabetes, cardiovascular disease, and obesity [20][21][22][23].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The use of tuakana and kaiarahi is consistent with the literature on community health workers (CHW) [51,52]. CHW are frequently employed with Indigenous communities in order to connect culturally with participants and systematic reviews demonstrate positive health gains from interventions delivered by CHW [31,32]. The current findings are also supportive of the benefits of using participatory research approaches to develop and adapt lifestyle interventions for risk factors associated with diabetes, cardiovascular disease, and obesity [20][21][22][23].…”
Section: Discussionsupporting
confidence: 76%
“…Both interventions used components from various lifestyle interventions (physical activity and nutrition) primarily the Diabetes Prevention Program [29,30]. Other elements of the intervention were developed through the co-design process although one key element (use of a peer or community health worker for support) has grounding in the extant literature [31,32]. These elements identified during the co-design process came from the participants as being motivating factors for their participation; differences between the two cohorts reflect this process.…”
Section: Interventionsmentioning
confidence: 99%
“…The majority of children in this work could not identify the appropriate course of action in case of a stroke and no child completed the test with a perfect score. Recent studies have shown that educational programs can have a positive impact, not only on children's stroke knowledge, but also on their extended families, since children can be leveraged as conduits and transfer stroke literacy to the family members (19)(20)(21)(22). We show that young children are not aware enough of the stroke symptomatology and thus suggest more school-based interventions that will deliver stroke knowledge to children.…”
Section: Discussionmentioning
confidence: 78%
“…It is well known that older adults are at greater risk of stroke than those in younger age groups (Gorelick, 2019; Teh et al, 2018; Tsivgoulis et al, 2018). In multigenerational families, older adults spend a substantial amount of time with their children or grandchildren, with grandparents often acting as secondary caregivers (Hill et al, 2017; Pulgaron et al, 2016). Women who do not give birth before the age of 30 are a typical example of older parents living in the family household.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a programme suited for the extended family is effective in promoting community health if it addresses both child and parental learning (Graybill et al, 2010; Ishigami et al, 2017; Kato et al, 2017; Morgenstern et al, 2007). Since previous studies have shown that intervention effects often cease when a health promotion programme is over (Morgenstern et al, 2007; Sakamoto et al, 2014), this programme aimed to deliver sustainable information by requiring children to disseminate stroke information to their extended family members, using posters, refrigerator magnets, stickers and other teaching aids (Hill et al, 2017). These aids act as positive reinforcers of programme participation and are integral to the programme’s effectiveness and sustainability.…”
Section: Introductionmentioning
confidence: 99%